2017
DOI: 10.1055/s-0043-115902
|View full text |Cite
|
Sign up to set email alerts
|

Operieren wir die Glaukome zu spät?

Abstract: As glaucoma specialists, we often ask ourselves why patients are referred so late for surgery. Usually the patient is referred in a far advanced stage of the disease after long-term conventional treatment with topical medications. By that time, substantial morphologic damage is present and the patient is disabled by far advanced visual field defects. In addition, decompensated intraocular pressure, despite maximal tolerated medical treatment, is seen. Delayed surgery due to late diagnosis is rather a rare even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…This would suggest that these conditions are either not present in rural communities or, more likely, underdiagnosed. Underreferring or referring patients too late for tertiary glaucoma care has been reported for both the VA and non-VA eye care professionals . Marks et al reported that there may be a significant difference in the management of glaucoma between optometrists and ophthalmologists.…”
Section: Discussionmentioning
confidence: 99%
“…This would suggest that these conditions are either not present in rural communities or, more likely, underdiagnosed. Underreferring or referring patients too late for tertiary glaucoma care has been reported for both the VA and non-VA eye care professionals . Marks et al reported that there may be a significant difference in the management of glaucoma between optometrists and ophthalmologists.…”
Section: Discussionmentioning
confidence: 99%
“…As of 2010, 1 in 15 blind people was blind due to glaucoma highlighting the increasing global burden of glaucoma ( 17 ). The correct management of patients with glaucoma requires scheduled monitoring of IOP and visual field so that prompt intervention can be made in case of progression of damage ( 18 ). There is a reduction in 81% of medical visits during the first few months of the pandemic, including cataracts (-97%), sleep apnea (-91%) and osteoarthrosis (-88%), and glaucoma (-88%) ( 19 , 20 ).…”
Section: Early Impact Of Covid-19 Outbreak On Glaucoma Carementioning
confidence: 99%